PENGARUH PENDAMPING PERSALINAN TERHADAP KEMAJUAN PERSALINAN PADA IBU BERSALIN DI PRAKTIK MANDIRI BIDAN PMB SE-KOTA TANJUNGPINANG - Nurniati Tianastia Rullyni; Vina Jayanti (Jurnal Ilmu dan Teknologi Kesehatan Terpadu)
WHO estimates that 10.7 million women die from childbirth. About 25-50% are related to labor and puerperal problems. One of the factors that influence labor is the mother's psychology, with the active role of the family during labor can reduce the incidence of complications and achieve safe labor, namely by paying attention to aspects of the mother's affection. Study purposes: Knowing the effect of labor companion on the progress of labor in maternal at PPM in Tanjungpinang city. The design in this study is a quasi-experiment with a post-test only control group design. The study was conducted at PPM throughout Tanjungpinang City, from September to November 2021. Respondents in this study were 68 mothers who indicated normal birth at PPM in Tanjungpinang City, 34 deliveries with a labor companion role and 34 deliveries without a labor companion role. The study tool used is an observation sheet. To find out whether there is an effect of the independent variable and the dependent variable, statistical analysis of the Independent Sample T-Test is used. The results showed that there is a companion effect on labor progress. it is recommended to apply the role of labor pendampimg to each birth process